Promotion of Papua “Merbau” Iron Wood (Eusideroxylon Zwagerii) through in-Vitro Tissue Culture - Roy Marthen Rahanra; Muhammad Imron; Dwi Yarmalinda (Budapest International Research and Critics University, 2022)
Papua's ironwood comes from the merbau plant that inhabits the forests of Papua, one of which is in the Yapen Islands Regency, Serui City. In conventional cultivating ironwood for commercial purposes, there are various problems. When using powder and soil, a lot of sawdust is needed. In addition, the time required for planting seeds to produce shoots that are ready to be planted in the field takes a very long time of about 9-12 months. The first step in the cultivation of merbau tissue culture is to find the right formula for growth regulators. Auxins and cytokines are the right steps to stimulate merbau wood growth. It seems that the role of auxin (IAA) and cytokinin (BAP) in Murashige and Skoog media on Merbau Wood using cotyledon and meristem explants with good concentrations for shoot and plantlet formation was 1.0 mg/l IAA and 5, 0 mg/l from the latest research using hormones including NAA, Chitin and BAP in Merbau (Eusideroxylon zwageri) wood culture. NAA concentration 1 mg/l (A4B5) formed shoots and callus, A4B1 (NAA 1 mg/l; BAP 0 mg/l) resulted in organogenesis and NAA concentration 0.2 mg/l without cytokinins (A2B1) produced multiple shoots. The interaction of the combination of auxin NAA 1 mg/l with BAP 0.6 mg/l (A4B7) gave the best response in embryosomatic formation in implanted explants. While the interaction of NAA 0.2 mg/l with Kinetic 2 mg/l (A3B3) resulted in shoots and callus. The interaction of the combination of auxin NAA 1 mg/l with BAP 0.6 mg/l (A4B7) gave the best response in embryosomatic formation in implanted explants. While the interaction of NAA 0.2 mg/l with Kinetic 2 mg/l (A3B3) resulted in shoots and callus. The interaction of the combination of auxin NAA 1 mg/l with BAP 0.6 mg/l (A4B7) gave the best response in embryosomatic formation in implanted explants. While the interaction of NAA 0.2 mg/l with Kinetic 2 mg/l (A3B3) resulted in shoots and callus.